FORMAÇÃO DA PERSONALIDADE RACISTA NO CONTEXTO FORMATIVO: ANÁLISES CONTEXTUAIS NO CAMPO DE ESTÁGIO - Juliana Silva Rando (2021)
We are social beings, therefore, this research aimed to understand how psychosocial aspects influence the development of a racist personality in a specific environment: school institutions, space for building identities in diversities. The research study had as theoretical assumption the studies developed within the Critical Theory (Th. W. Adorno, in particular) and studies related to human development and relationships with the learning process. The latter produced by psychologists as theoretical contribution towards promoting the understanding of the individuals’ psychosocial development. From this theoretical framework, we will list categories pertinent to the study on screen that include the institutional setting and its architectonic dimensions; diversities; games; interpersonal relationships and pedagogical practices, completing five categories of analysis. To reach this goal, the study made use of documentary qualitative research with analysis. The observations regarding Child Education institutions were made through experiences in the mandatory internships for the training of pedagogues in the Universidade Federal de Mato Grosso do Sul- UFMS, Campus de Três Lagoas/MS, in the years of 2015 and 2016. These observations were appropriated due to the COVID-19 pandemics that impeded the production of a current corpus, restricting the field research in the year of 2020. The choice of observations on Child Education with children at four to six years old (4-6 years old) was made, since we understand that this is the time essential to childhood development and socialization. On top of that, we understand that at this age range children have certain mastery over their speech and are able to express, to some extent, their ideas. From the results of observations, we developed categories of analysis to learn better about the school daily life. The research left from questioning how the context of Child Education takes part in the development of the racist personality? Once we are not racist at birth, but we become. Conclusions indicate that Child Education has indeed a relevant role in the development and dissolution of the racist personality, since it has as target children in the personality development process. We can say that some practices observed powered the formation of non-segregationist personalities; however, the promotion of racist and discriminatory practices supported by covert racism became evident. The analyses enabled us to learn as well about the actual need of installing an educational environment, concerning Child Education, an environment rich in routines permeated by the structuration of practices that talk about providing care and educating indissociably, promoting the need of a everyday life, within these institutions, founded on integrative non-judgmental anti-discriminatory practices throughout pedagogical and recreational activities. The need of these practices becomes more elucidated through ergonomics, posters, and care offered to children. In addition, it was possible to observe that generational nomenclatures, speeches, games, among others, are also loaded with ideologies that reaffirm racism. Therefore, we must invest openly and intentionally in an antiracist education as utopia, for the development of children in their childhood, becoming evident the need to break with educational practices, since the early childhood, anchored in Eurocentric precepts that enable a differentiated attention towards children according to their phenotypic characteristics. Key words: Racist personality. Childhood. Child Education.